Study of Camels RBCs and Elemental Analysis Using Scanning Electron Microscopy (SEM) and Elemental Dispersive Spectroscopy (EDS) in Southern Iraq - Amer Al Hasan; Nameer Al Zubaidi; Fatima Mustafa (Basrah Journal of Veterinary Research)
The current study was designed to assess some critical mineral elements concentration in the serum of camels using advanced methods like Energy Dispersive Spectroscopy analysis (SEM-EDS) using scanning electron microscope of minute camel’s blood. The present study was conducted on forty-eight healthy adult males and females of camel (Camelus dromedarius) aged three to five years in three southern governorates of Iraq: Basra, Thi-Qar and Muthana (6 males and 10 females per governorate). Blood samples were applied to field emission scanning electron microscopy (FE-SEM) to recognize the essential cellular morphological properties found in camel’s RBCs that assist camels to adaptation on harsh condition. While, serum was subsequently assayed for elemental analysis by energy dispersive spectroscopy (EDS). The SEM images of RBCs showed a smooth surface with a circumference invagination referred to tropical waist with difference in length and width of RBCs between male and female. While, EDS percentage atomic concentrations study of camel’s serum revealed different amount of essential, heavy and rare trace elements in both sexes from the Basra and Thiqar governorate and different levels in essential elements in the serum of both sexes of Thiqar and Muthana governorates.